Pole piece and preparation method thereof, battery cell, battery and electric equipment

By stacking the first active structure and the second active structure with different particle sizes on the foil to form straight pores, the problems of low diffusion rate of lithium ion liquid phase and high tortuosity in the existing electrode structure are solved, and higher battery dynamics performance is achieved.

CN119833565APending Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311434949.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing electrode structure is difficult to effectively improve the diffusion rate of lithium ion liquid phase and reduce the tortuosity of the electrode plate, affecting the dynamic performance of the battery.

Method used

By stacking the connected first active structure and the second active structure on the foil, the average particle size of the first active material is greater than the average particle size of the second active material, and a straight pore is formed to increase the liquid phase diffusion rate of the lithium ions and reduce the tortuosity of the pole sheet.

Benefits of technology

While ensuring the active site, the liquid phase diffusion rate of lithium ions is significantly improved, the tortuosity of the electrode sheet is reduced, and the dynamic performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833565A_ABST
    Figure CN119833565A_ABST
Patent Text Reader

Abstract

The invention relates to a pole piece and a preparation method thereof, a battery cell, a battery and electric equipment, the pole piece comprises a foil and an active material layer, and the active material layer is laminated on at least one surface of the foil; the active material layer comprises a first active structure and a second active structure which are connected; the first active structure comprises a first active material, the second active structure comprises a second active material, and the average particle size of the first active material is larger than that of the second active material. According to the pole piece, the first active structure and the second active structure which are connected are arranged, the average particle sizes of the first active material and the second active material are different, and a straight-through pore can be formed at the intersection of the first active material and the second active material, so that active sites can be ensured, the tortuosity of the pole piece can be reduced, and the liquid phase diffusion rate of lithium ions can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a pole piece and a preparation method thereof, a battery cell, a battery and an electrical device. Background Art

[0002] Power batteries continue to make improvements and breakthroughs in energy density and power density. Current electrode structure designs are all focused on higher surface density and fast charging performance. The pore structure of the electrode is of great significance to the infiltration of the electrolyte and the liquid phase transport of lithium ions. How to achieve high dynamic performance through simple process design and particle matching is the key to optimizing the electrode structure.

[0003] At present, the common electrode design is to adopt a double-layer coating scheme. According to the unevenness of the electrochemical reaction inside the electrode, small particles with large reaction surface area are placed on the upper layer to make full use of the active surface area. However, how to increase the liquid phase diffusion rate of lithium ions and reduce the tortuosity of the electrode has not been well solved. Summary of the invention

[0004] The purpose of the present application is to provide a pole piece and a method for preparing the same, a battery cell, a battery and an electrical device, which can effectively improve the liquid phase diffusion rate of lithium ions and reduce the tortuosity of the pole piece while ensuring the active sites.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a pole piece, comprising a foil and an active material layer, wherein the active material layer is stacked on at least one side of the foil; the active material layer comprises a first active structure and a second active structure which are connected to each other; the first active structure comprises a first active material, the second active structure comprises a second active material, and the average particle size of the first active material is greater than the average particle size of the second active material.

[0007] In one embodiment, the average particle size of the first active material is D1, and the average particle size of the second active material is D2, satisfying: 0.45≤D2 / D1≤0.75.

[0008] In one embodiment, the first active structure and the second active structure are both multiple, and the multiple first active structures and the multiple second active structures are alternately arranged on the surface of the foil.

[0009] In one embodiment, the average particle size D1 of the first active material satisfies: 0.9 μm≤D1≤1.6 μm.

[0010] In one embodiment, the first active structure is connected to the second active structure in a first direction, the width of the first active structure in the first direction is W1, the width of the second active structure in the first direction is W2, and 0.8≤W1 / W2≤1.2 is satisfied.

[0011] In one embodiment, the material of the first active structure is the same as the material of the second active structure.

[0012] In a second aspect, the present application also provides a method for preparing an electrode sheet, comprising: providing a foil; stacking an active material layer on at least one side of the foil; the active material layer comprises a first active structure and a second active structure that are connected; the first active structure comprises a first active material, the second active structure comprises a second active material, and the average particle size of the first active material is greater than the average particle size of the second active material. First average particle size

[0013] In one embodiment, a first active structure is stacked on the foil, and a second active structure is also stacked on the foil, including: providing a first coating die and a second coating die; providing a slurry, the slurry consisting of an active material, a binder and a conductive agent; the slurry includes a first slurry and a second slurry; the first coating die coats the first slurry on the foil to form the first active structure, and the second coating die coats the second slurry on the foil to form the second active structure.

[0014] In one embodiment, the slurry includes: the active material is a positive electrode active material, the content of the positive electrode active material is A, the content of the binder is B, and the content of the conductive agent is C, satisfying: A:B:C=100:(2.0-2.5):(0.6-1.2).

[0015] In a third aspect, the present application further provides a battery cell, comprising a diaphragm and a pole piece as described in any one of the embodiments of the first aspect, wherein the pole piece and the diaphragm are stacked.

[0016] In a fourth aspect, the present application further provides a battery, comprising a housing and the battery cell as described in the third aspect, wherein the battery cell is accommodated in the housing.

[0017] In a fifth aspect, the present application further provides an electrical device, comprising an electrical device and a battery as described in the fourth aspect, wherein the battery supplies power to the electrical device.

[0018] By setting up a connected first active structure and a second active structure, the particle sizes of the first active material in the first active structure and the second active material in the second active structure are different, and a straight pore can be formed at the intersection of the two, which can reduce the tortuosity of the electrode while ensuring the active site and improve the liquid phase diffusion rate of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 is a schematic diagram of the cross-sectional structure of a pole piece of an embodiment;

[0021] Figure 2 is a schematic diagram of the cross-sectional structure of a first active structure and a second active structure of an embodiment;

[0022] Figure 3 is a flow chart of a method for preparing a pole piece according to an embodiment;

[0023] Figure 4 The present invention is a flow chart of one of the steps in a method for preparing a pole piece according to an embodiment.

[0024] Description of reference numerals:

[0025] 100-pole piece;

[0026] 10 - foil, 20 - first active structure, 21 - first active material, 30 - second active structure, 31 - second active material, 40 - ion channel. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0029] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0030] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0031] The embodiment of the present application provides an electric device, including an electric device and a battery in the embodiment of the present application, and the battery supplies power to the electric device. The electric device can be an electric vehicle, a hybrid vehicle, a base station, a household power load, etc. The electric device uses the battery in the embodiment of the present application, which can improve the liquid phase diffusion rate of lithium ions in the battery while ensuring active sites, thereby improving battery performance.

[0032] The present application also provides a battery, including the battery cell in the present application. The battery can be a square laminated battery, an energy storage battery, and the like.

[0033] The battery also includes a shell, which includes a bottom plate and a plurality of side plates, the side plates are connected to the bottom plate and enclosed to form a receiving cavity. The receiving cavity is open at one end opposite to the bottom plate, and the battery cell is received in the receiving cavity.

[0034] Optionally, the shell can be an integrated structure, that is, the bottom plate and the side plate are an integrated structure made by an integrated molding process, and the integrated molding process can be stamping, casting, etc., without limitation. The shell can also be a split structure, and the side plate and the bottom plate can be connected and fixed by welding, bonding, clamping, screwing, etc. The wall thickness of the shell can be roughly uniform everywhere, that is, the thickness of the side plate can be roughly uniform, and the thickness of the bottom plate and the side plate can also be roughly the same.

[0035] The battery also includes a cover plate, which is connected to the opening of the shell to close the accommodating cavity. The connection between the cover plate and the shell can be welding, bonding, clamping, screwing, etc., without limitation. The shape of the cover plate can be roughly the same as that of the bottom plate.

[0036] The battery adopts the battery cell in the embodiment of the present application, which can effectively increase the liquid phase diffusion rate of lithium ions and improve battery performance.

[0037] An embodiment of the present application also provides a battery cell, including a diaphragm and a pole piece in the present application, wherein the pole piece and the diaphragm are stacked.

[0038] Optionally, the electrode sheet includes a positive electrode sheet and a negative electrode sheet, and the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence.

[0039] In lithium-ion batteries, the solid-phase and liquid-phase transport modes of lithium ions determine the dynamic performance of the battery. The solid-phase transport mode is the movement of lithium ions in the positive and negative electrode materials, while the liquid-phase transport mode is the movement of lithium ions in the electrolyte. It can be understood that in lithium-ion batteries, the faster the movement speed of lithium ions, the higher the efficiency of lithium ion deintercalation between the positive and negative electrodes, so lithium-ion batteries can also achieve faster charging speeds.

[0040] In the solid phase transmission mode, the particle size of a single particle of the electrode material determines the transmission distance of lithium ions, and therefore also determines the transmission efficiency of lithium ions. Because when the movement speed of lithium ions is the same, the smaller the particle size of the material particles, the shorter the solid phase transmission distance of lithium ions and the shorter the solid phase transmission time of lithium ions. Therefore, smaller particle size of positive electrode material particles is beneficial to the solid phase transmission efficiency.

[0041] In the liquid phase transmission mode, lithium ions move between the electrode material particles through the electrolyte. So it is understandable that when the electrolyte flows more smoothly, the lithium ion transmission efficiency is higher. The smaller the particle size of the electrode material particles, the closer the particles are, resulting in greater resistance to the flow of the electrolyte and lower lithium ion transmission efficiency.

[0042] When the particle size of the positive and negative electrode materials of the battery is small, it can not only shorten the solid-phase transmission distance of lithium ions, but also have a higher reactive surface area, but it will increase the side reactions and liquid-phase transmission barriers, while the effect of larger material particle size is the opposite. Therefore, it is difficult to improve the solid-phase and liquid-phase transmission of lithium ions at the same time by modifying the particle size distribution of the main material alone.

[0043] This application proposes a lateral design structure. Different from the upper and lower layers of double-layer coating, the lateral design structure aims to balance the active sites and pore passages of the particles in the horizontal direction. While small-size particles improve the solid-phase transmission efficiency, they can increase the liquid-phase transmission of lithium ions and electrolyte infiltration, and reduce the tortuosity of the electrode. Tortuosity is the degree of curvature of the path through which the electrolyte meanders in the electrode layer. It can be understood that the higher the tortuosity of the electrode layer, the more tortuous the flow path; the lower the tortuosity of the electrode layer, the straighter the flow path. Therefore, the higher the tortuosity, the lower the liquid-phase transmission efficiency; the lower the tortuosity, the higher the liquid-phase transmission efficiency.

[0044] Please refer to Figure 1 and Figure 2The embodiment of the present application provides a pole piece 100, comprising a foil 10 and an active material layer, wherein the active material layer is stacked on at least one side of the foil 10. The active material layer comprises a first active structure 20 and a second active structure 30 which are connected to each other; the first active structure 20 comprises a first active material 21, the second active structure 30 comprises a second active material 31, and the average particle size of the first active material 21 is greater than the average particle size of the second active material 31.

[0045] Optionally, when the electrode sheet 100 is a positive electrode sheet 100, the foil material 10 is an aluminum foil; when the electrode sheet 100 is a negative electrode sheet 100, the foil material 10 is a copper foil.

[0046] Optionally, the number of the first active structures 20 may be one or more; the number of the second active structures 30 may be one or more, and there is no specific limitation.

[0047] Optional, such as Figure 1 As shown, the first active structure 20 and the second active structure 30 are connected in a first direction X, and the first direction X is a direction perpendicular to the coating direction and parallel to the surface of the foil 10 .

[0048] The electrode 100 in the embodiment of the present application is provided with a first active structure 20 and a second active structure 30 connected to each other. In the direction perpendicular to the foil 10, the particle sizes of the first active material 21 and the second active material 31 are different, and a straight pore can be formed at the intersection of the two. While ensuring the active sites, the tortuosity of the electrode 100 can be reduced, thereby improving the liquid phase diffusion rate of lithium ions.

[0049] Optionally, the average particle size of the first active material 21 is D1, and the average particle size of the second active material 31 is D2, satisfying: 0.45≤D2 / D1≤0.75.

[0050] Among them, D1 and D2 can be directly tested by the particle size analyzer of the powder material. 50 can also be obtained by measuring the particle size of the corresponding area in the pole piece 100 through the SEM image, and using statistical methods to obtain the average particle size.

[0051] Optionally, at the interface between the first active structure 20 and the second active structure 30, an ion channel 40 is formed between the first active material 21 and the second active material 31, for the electrolyte to carry lithium ions and flow freely. It can be understood that due to the difference in particle size between the first active material 21 and the second active material 31, the arrangement of the two at the interface is relatively disordered, so the tortuosity of the formed ion channel 40 is lower than the tortuosity of the channel formed by the stacking of the first active material 21 or the second active material 31 itself, which facilitates the flow of the electrolyte.

[0052] Optionally, the ratio of the second average particle diameter D2 to the first average particle diameter D1 can be 0.5, 0.6, 0.7, etc., without limitation.

[0053] By setting the first active material 21 and the second active material 31, the average particle size of the first active material 21 is D1, and the average particle size of the second active material 31 is D2, satisfying: 0.45≤D2 / D1≤0.75, a straight pore can be formed at the junction of the first active material 21 and the second active material 31, which can reduce the tortuosity of the electrode 100 while ensuring the active site, and improve the liquid phase diffusion rate of lithium ions.

[0054] Optionally, there are multiple first active structures 20 and multiple second active structures 30 , and the multiple first active structures 20 and the multiple second active structures 30 are alternately arranged on the surface of the foil 10 .

[0055] Optionally, the number of the first active structures 20 and the number of the second active structures 30 may be the same, or may differ by 1. For example, there are 3 first active structures 20 and 3 second active structures 30; or, there are 4 first active structures 20 and 3 second active structures 30; or, there are 3 first active structures 20 and 4 second active structures 30, etc., without specific limitation.

[0056] For example, please refer to Figure 1 and Figure 2 There are two first active structures 20 and two second active structures 30 , and the two first active structures 20 and the two second active structures 30 are alternately arranged on the surface of the foil 10 .

[0057] Optionally, the number of the first active structures 20 and the number of the second active structures 30 may be 2 to 10. Since the coating process is more complicated when the number of the first active structures 20 and the second active structures 30 is large, the number of the first active structures 20 and the second active structures 30 is preferably 4 to 6.

[0058] By providing a plurality of first active structures 20 and a plurality of second active structures 30 , more interfaces between the first active material 21 and the second active material 31 can be formed, thereby reducing the tortuosity of the pole piece 100 .

[0059] Optionally, the first average particle size D1 satisfies: 0.9 μm≤D1≤1.6 μm.

[0060] Optionally, the value of the first average particle size D1 can be 0.9 μm, 1.2 μm, 1.5 μm, etc., without limitation. Correspondingly, the value of the second average particle size D2 must satisfy 0.45≤D2 / D1≤0.75, and 0.9 μm≤D1≤1.6 μm. Exemplarily, if D2 / D1 is 0.5, then the value of the second average particle size D2 corresponding to the first average particle size D1 can be 0.45 μm, 0.6 μm, 0.75 μm, etc., without limitation.

[0061] By setting the size of the first average particle size D1 and limiting the size of the second average particle size D2 in accordance with the ratio of the first average particle size D1 to the second average particle size D2, the first average particle size D1 and the second average particle size D2 are made to be of a more appropriate size, while generating more through pores and ensuring abundant active sites, which is beneficial to improving the solid phase transport efficiency.

[0062] Optional, such as Figure 1 As shown, the first active structure 20 is connected to the second active structure 30 in the first direction X, the length of the first active structure 20 extending in the first direction X is the first width W1, and the length of the second active structure 30 extending in the first direction X is the second width W2, satisfying: 0.8≤W1 / W2≤1.2.

[0063] Optionally, the value of W1 / W2 may be 0.9, 1, 1.1, etc., without limitation.

[0064] By setting the first width W1 of the first active structure 20 in the first direction X and the second width W2 of the second active structure 30 in the first direction X, W1 and W2 can be made substantially the same, rather than completely the same, to avoid increasing the difficulty of processing. At the same time, it can also ensure that the vertical through holes in the pole piece are more evenly distributed, thereby ensuring the electrochemical performance of the battery.

[0065] Optionally, the material of the first active structure 20 is the same as the material of the second active structure 30 .

[0066] Optionally, when the electrode sheet 100 is a positive electrode sheet 100, the first active structure 20 and the second active structure 30 both include components such as positive electrode active materials, conductive agents, and binders. The present application does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive electrode active material can be a phosphate positive electrode active material and a ternary positive electrode active material, which can be one or more of lithium cobalt oxide, lithium manganate, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide; the conductive agent can be one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes; the binder can be one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives, without specific limitation.

[0067] Optionally, when the electrode sheet 100 is a negative electrode sheet 100 , the first active structure 20 and the second active structure 30 both include components such as negative electrode active materials, conductive agents, and binders, and there is no specific limitation.

[0068] By setting the material of the first active structure 20 to be the same as that of the second active structure 30 , it is avoided that the materials of the first active structure 20 and the second active structure 30 are different and affect each other, thereby facilitating the transmission of lithium ions.

[0069] The present application also provides a method for preparing the pole piece 100. Figure 3 , specifically including the following steps:

[0070] S10, providing a foil 10;

[0071] S20 , laminating an active material layer on at least one side of the foil 10 .

[0072] Specifically, the active material layer includes a first active structure 20 and a second active structure 30 which are connected to each other, the first active structure 20 includes a first active material 21, the second active structure 30 is connected to the first active structure 20, the second active structure 30 includes a second active material 31, and the average particle size of the first active material 21 is greater than the average particle size of the second active material 31.

[0073] Optionally, the average particle size of the first active material 21 is D1, and the average particle size of the second active material 31 is D2, satisfying: 0.45≤D2 / D1≤0.75.

[0074] By providing a connected first active structure 20 and a second active structure 30 on the foil 10, the particle sizes of the first active material 21 and the second active material 31 are different in the direction perpendicular to the foil 10, and straight pores can be formed at the intersection of the two, which can reduce the tortuosity of the electrode 100 while ensuring the active sites, thereby improving the liquid phase diffusion rate of lithium ions.

[0075] Optionally, an active material layer is stacked on at least one side of the foil 10, see Figure 4 , specifically including the following steps:

[0076] S21, providing a first coating die and a second coating die;

[0077] S22, providing a slurry, wherein the slurry is composed of an active material, a binder, a conductive agent, and a solvent, and the slurry includes a first slurry and a second slurry;

[0078] S23 , the first coating die head coats the first slurry on the foil material 10 to form the first active structure 20 , and the second coating die head coats the second slurry on the foil material 10 to form the second active structure 30 .

[0079] Optionally, the first coating die head and the second coating die head have the same structure, and the first slurry and the second slurry are made of the same material.

[0080] Optionally, the first slurry includes a first active material 21, and the average particle size of the first active material 21 is D1; ​​the second slurry includes a second active material 31, and the average particle size of the second active material 31 is D2, satisfying: 0.45≤D2 / D1≤0.75.

[0081] Optionally, the first coating die head coats the first slurry on the foil 10, and the second coating die head coats the second slurry on the foil 10, and the electrode 100 is prepared by baking and rolling. At this time, the area coated with the first slurry forms the first active structure 20, and the area coated with the second slurry forms the second active structure 30. Finally, the electrode 100 is rolled. Figure 1 The structure of the lateral pole piece 100 is shown.

[0082] By providing a first coating die and a second coating die, the first coating die coats the first slurry on the foil 10 , and the second coating die coats the second slurry on the foil 10 , so as to obtain the first active structure 20 and the second active structure 30 .

[0083] Optionally, the slurry provided includes: the active material is a positive electrode active material, the content of the positive electrode active material is A, the content of the binder is B, and the content of the conductive agent is C, satisfying: A:B:C=100:(2.0-2.5):(0.6-1.2). The above contents all represent the mass of the substance.

[0084] Optionally, the positive electrode active material is lithium iron phosphate particles, the binder is selected from polytetrafluoroethylene, the conductive agent is carbon black, and the ratio of the positive electrode active material A, the binder B, and the conductive agent C is A:B:C=100:2.2:0.8 respectively.

[0085] It can be understood that since the positive electrode active material accounts for a large proportion of the active material, the conductive agent and the binder can be ignored compared to the active material. Therefore, in this application, only the average particle size D1 of the first active material 21 and the average particle size D2 of the second active material 31 are controlled. Among them, the average particle size D1 of the first active material 21 and the average particle size D2 of the second active material 31 can be directly tested by a particle size analyzer for testing powder materials. 50 can also be obtained by measuring the particle size of the corresponding area in the pole piece 100 through the SEM image, and using statistical methods to obtain the average particle size.

[0086] By setting appropriate slurry components and ratios, more through pores are generated at the interface between the first active structure 20 and the second active structure 30, while abundant active sites are ensured, which is beneficial to improving the solid phase transmission efficiency.

[0087] The technical solution of the present invention is described in detail below through specific embodiments.

[0088] Example 1

[0089] The positive electrode sheet of this embodiment includes a foil, a first active structure and a second active structure, wherein the foil is an aluminum foil, the first active structure includes a first active material, and the average particle size D1 of the first active material is 1.2 μm; the second active structure includes a second active material, and the average particle size D2 of the second active material is 0.36 μm, and D2 / D1=0.3.

[0090] 1) Ingredients: a first slurry for forming a first active structure and a second slurry for forming a second active structure are respectively prepared; each slurry contains an active material, a conductive agent, a binder and a solvent, the average particle size D1 of the first active material in the first slurry is 1.2 μm, and the average particle size D2 of the second active material in the second slurry is 0.36 μm; wherein the active materials are all lithium iron phosphate particles, the binder is selected from polytetrafluoroethylene, the conductive agent is carbon black, and the ratio of the active material, the binder and the conductive agent is 100:2.2:0.8 respectively.

[0091] 2) Layer coating: coating the first slurry and the second slurry on the surface of the aluminum foil respectively to form a first active structure and a second active structure connected to each other, and preparing a positive electrode sheet through baking and rolling.

[0092] Example 2

[0093] The positive electrode sheet of this embodiment includes a foil, a first active structure and a second active structure. The difference between this embodiment and embodiment 1 is that the average particle size D1 of the first active material is 0.6 μm; the average particle size D2 of the second active material is 0.3 μm, and D2 / D1=0.5.

[0094] Example 3

[0095] The positive electrode sheet of this embodiment includes a foil, a first active structure and a second active structure. The difference between this embodiment and embodiment 1 is that the average particle size D1 of the first active material is 1.2 μm; the average particle size D2 of the second active material is 0.6 μm, and D2 / D1=0.5.

[0096] Example 4

[0097] The positive electrode sheet of this embodiment includes a foil, a first active structure and a second active structure. The difference between this embodiment and embodiment 1 is that the average particle size D1 of the first active material is 1.5 μm; the average particle size D2 of the second active material is 0.75 μm, and D2 / D1=0.5.

[0098] Example 5

[0099] The positive electrode sheet of this embodiment includes a foil, a first active structure and a second active structure. The difference between this embodiment and embodiment 1 is that the average particle size D1 of the first active material is 1.2 μm; the average particle size D2 of the second active material is 0.96 μm, and D2 / D1=0.8.

[0100] Example 6

[0101] The positive electrode sheet of this embodiment includes a foil, a first active structure and a second active structure. The difference between this embodiment and embodiment 1 is that the average particle size D1 of the first active material is 2.0 μm; the average particle size D2 of the second active material is 1.6 μm, and D2 / D1=0.8.

[0102] Comparative Example 1

[0103] The positive electrode sheet in this comparative example includes a foil, a first active structure and a second active structure. The difference between this example and Example 1 is that the average particle size D1 of the first active material is 1.2 μm; the average particle size D2 of the second active material is 1.2 μm, and D1=D2.

[0104] Table 1 is a summary table of the parameters of the positive electrode sheets of the above-mentioned embodiments and comparative examples.

[0105] Table 1

[0106]

[0107] Pole performance test:

[0108] The 50% SOC DC internal resistance (DCI R) test method is as follows:

[0109] At room temperature 25±5℃, the battery was discharged at 1 / 3C constant current to 2.0V, charged at 1 / 3C constant current to 50% SOC, and left for 30min; discharged at 1.5C constant current for 30s, and the 50% SOC DC internal resistance (DCIR) was detected.

[0110] The liquid phase diffusion impedance test method is as follows:

[0111] The two positive plates and the separator are assembled into a pole core in sequence; then the pole core is placed in an outer packaging shell, baked, injected with electrolyte, and after packaging, impregnation and other processes, a liquid phase diffusion impedance battery is obtained. Liquid phase diffusion impedance testing is performed using an electrochemical workstation within a frequency range of 300,000 Hz-0.05 Hz.

[0112] The electrochemical properties of the positive electrode sheets prepared in Examples 1-6 and Comparative Example 1 were characterized. Table 2 shows the electrode sheet information, including the 50% SOC DC internal resistance of the electrode sheet, the liquid phase diffusion resistance of the symmetrical battery, and the fast charging test data.

[0113] Table 2

[0114]

[0115]

[0116] It can be seen from the experimental results of Example 2, Example 3, and Example 4 in Table 1 and Table 2 that, when D2 / D1 remains unchanged, by changing the size of D1 and D2, the impedance and liquid phase diffusion capacity of the electrode will change. A smaller particle size will result in a significantly larger liquid phase diffusion resistance than the same electrode, which will affect the efficiency of lithium ion deintercalation in the electrode, which is not conducive to improving the charge and discharge performance of the battery. Therefore, in Table 2, since the average particle size D1 of the first active material of Example 2 is smaller than the range provided in this application, its rate discharge retention rate is slightly inferior to that of Example 3 and Example 4.

[0117] From the experimental results of Example 1, Example 3, and Example 5 in Table 1 and Table 2, it can be seen that when the average particle size D1 of the first active material remains unchanged, by changing the size ratio of the average particle size D1 of the first active material to the average particle size D2 of the second active material, the impedance and liquid phase diffusion capacity of the pole piece will also change. It is not difficult to see that the 50% SOC DC internal resistance of Example 3 is smaller, the liquid phase diffusion impedance is lower, and it has a higher rate discharge retention rate. This is because it directly forms a through hole at the interface of large and small particles, which increases the infiltration of the electrolyte and ion transmission, while also taking into account the material reaction active sites.

[0118] It can be seen from the experimental results of Examples 1-6 and Comparative Example 1 in Tables 1 and 2 that when the average particle sizes of the first active material and the second active material are the same, their internal resistance and liquid phase diffusion impedance are both at a poor level, and their rate discharge retention rate is also not as good as that of Examples 1-6. This also illustrates that by satisfying the setting of the first active structure and the second active structure, the average particle size D1 of the first active material, the average particle size D2 of the second active material, and the ratio D2 / D1 of the two are within the scope of the present application, ensuring that the gaps at the interface of the particles form micron-level straight-through pores, increasing the liquid phase transmission of lithium ions and the electrolyte infiltration, while taking into account the rich active sites, so as to obtain a positive electrode sheet with better electrochemical performance.

[0119] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0120] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A pole piece, characterized in that: include: Foil, An active material layer is stacked on at least one side of the foil; The active material layer includes a first active structure and a second active structure which are connected to each other; the first active structure includes a first active material, the second active structure includes a second active material, and the average particle size of the first active material is greater than the average particle size of the second active material.

2. The pole piece according to claim 1, characterized in that: The average particle size of the first active material is D1, and the average particle size of the second active material is D2, satisfying: 0.45≤D2 / D1≤0.

75.

3. The pole piece according to claim 1, characterized in that: There are a plurality of the first active structures and a plurality of the second active structures, and the plurality of the first active structures and the plurality of the second active structures are alternately arranged on the surface of the foil.

4. The pole piece according to claim 2, characterized in that: The average particle size D1 of the first active material satisfies: 0.9 μm≤D1≤1.6 μm.

5. The pole piece according to claim 1, characterized in that: The first active structure is connected to the second active structure in a first direction, the width of the first active structure in the first direction is W1, the width of the second active structure in the first direction is W2, and the following conditions are satisfied: 0.8≤W1 / W2≤1.

2.

6. The pole piece according to claim 1, characterized in that: The material of the first active structure is the same as the material of the second active structure.

7. A method for preparing a pole piece, characterized in that: include: Provide foil; An active material layer is laminated on at least one side of the foil; The active material layer includes a first active structure and a second active structure which are connected to each other; the first active structure includes a first active material, the second active structure includes a second active material, and the average particle size of the first active material is greater than the average particle size of the second active material.

8. The method for preparing a pole piece according to claim 7, characterized in that: An active material layer is stacked on at least one side of the foil, comprising: Providing a first coating die and a second coating die; Providing a slurry, wherein the slurry is composed of an active material, a binder, a conductive agent, and a solvent; the slurry includes a first slurry and a second slurry; The first coating die coats the first slurry on the foil to form the first active structure, and the second coating die coats the second slurry on the foil to form the second active structure.

9. The method for preparing a pole piece according to claim 8, characterized in that: The slurry is provided including: the active material is a positive electrode active material, the content of the positive electrode active material is A, the content of the binder is B, the content of the conductive agent is C, and the following conditions are satisfied: A:B:C=100:(2.0-2.5):(0.6-1.2).

10. A battery cell, characterized in that: It comprises a diaphragm and a pole piece as claimed in any one of claims 1 to 6, wherein the pole piece and the diaphragm are stacked.

11. A battery, characterized in that: The invention comprises a shell and the battery core as claimed in claim 10, wherein the battery core is accommodated in the shell.

12. An electrical equipment, characterized in that: It comprises an electric device and the battery as claimed in claim 11, wherein the battery supplies power to the electric device.